The chalcolithic of the Baixa Estremadura : contributions for an essay, in reference to Leceia (Oeiras) - Cardoso, João Luís (2016)
The seventeen annual seasons of excavations conducted at the prehistoric settlement of Leceia since 1983 have produced a large assemblage of stratified materiais, as well as numerous field observations, capable of constituting the basis and reference of future works at other archaeological sites in the region (for a complete bibliography on Leceia, published up to 1998, see CARDOSO, 1997/1998). ln fact the record obtained there shows an evolution, over more than one thousand years, of a dynamic and complex society, exploring in increasingly more exhaustive ways the available natural resources. It was the agricultural potential, enhanced through lhe successive improvement of the technologies of production, which allowed for lhe creation of an economic surplus able to support the exchange of products and raw materials with other regions, these exchanges being well-documented by the nature and typology of lhe artifacts recovered. We are, therefore, faced with a community clearly open to exchanges of products and of goods, strongly connected to a well- defined territory. The aforementioned economic relations established by the inhabitants of Leceia with the exterior made possible the introduction of new technologies (copper metallurgy is one example) and affirmed itself, as well, at the more abstract level of magico-religious superstructure, as can be concluded by the nature and typology of the ideo-artifacts recovered, which clearly show the integration of their possessors within a world of Mediterranean cultural roots. On the other hand, there exists a relationship between the architectural complexity and the existence of semi-specialized intramural areas, of production or storage, which are found clearly documented at Leceia by diverse structures of production. Leceia constituted, in this way, the center of a stable and sedentary population grouping, linked togelher with other settlements, of smaller size, with whom it was united probably by a common origin, by consanguinity. What is the explanatory model for the genesis and evolution of this society, between the middle of the 4 th and the end of the 3rd millennia BC? It appears, above all, to have been characterized by a social process influenced by exogenous influence, conditioned by economic conditions and available natural resources, whose interaction (PARREIRA, 1990, p. 29) resulted in a society with marked specificities, precociously evoIved, articulated with other human groups, in a transregional perspective. Based on lhe available data, it is usual to consider, for the Chalcolilthic of lhe Estremadura, three principal cultural phases. Such phases can be found stratified at Leceia in a paradigmatic form, corresponding to archaeological levels with dilferent artifactual characteristics and contents. Among these stand out the ceramics, of which some types can be understood as true markers, or stratigraphic fossils, to use the expression from the geological worId, with expression and validity at Leceia, as in other settlements of the same cultural area. We will take a Iook at, therefore, the principal characteristics of these phases, identified stratigraphically.